The Maternal Imagination of Film and Film Theory - Bliss, Lauren; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
This book challenges common sense understandings of the unconscious effects of cinema and visual culture. It explores the castrating power of the early modern witch and the historical belief that pregnant women could manipulate and distort body image as figurative analogies for feminist theories of objectification and the male gaze. Through developing this history as an impure but lively analogy, this book serves as a provocation against the dominant imagining of objectification. It offers innovative analyses of a wide-ranging selection of films and topics including Joyce Wieland s Water Sark (1964) and its resonance with the works of John Cage and Stan Brakhage; the documentary Histoires d A (History of Abortion, 1973), which contributed to the successful legalisation of abortion in France; the Hong Kong horror film Dumplings (Jiaozi, 2004), where foetal cannibalism serves up an image of censorship; and the dual productions The Book of Mary (Le livre de Marie) and Hail Mary (Je vous salue, Marie, 1985) by Anne-Marie Miéville and Jean-Luc Godard that figure a self-reproducing virgin who hears herself while remaining a virgin, unseen.
Introduction: Pregnant Illusions and the Natural Body -- Ch1 Conceiving the Cinematic Body -- Ch2 The Witchcraft of Cinema -- Ch3 Pregnant Illusions: Natural Magic and the Imagination -- Ch4 Sound and Vision: The Cinematic Figuration of the Virgin Mary -- Ch5 Conceiving the Cinematic Body -- Ch6 The Pregnancy of the Cinematic Public Sphere.
Keywords: Motion pictures; Culture; Gender; Film Theory; Culture and Gender